Swapping Stories : Folktales from Louisiana - Harvison, C. Renee; Owens, Maida; Lindahl, Carl, 1947- (Book collections on Project MUSE., 1997)
Here are more than two hundred oral tales from some of Louisiana's finest storytellers. Transcribed from on-the-spot presentations, this collection of narratives includes many genres (ghost stories, tall tales, political anecdotes, animal tales, myths, magic tales, buried treasure tales, and reminiscences of small-town life). It also represents diverse voices (Cajuns, Creoles, Native Americans, African Americans, and Louisianans of Hungarian, Italian, and Vietnamese descent) and all regions of this storytelling state. Given special focus are Harold Talbert, Lonnie Gray, Bel Abbey, Ben Guine, and Enola Matthews - whose wealth of imagination, memory, and artistry demonstrates the depth as well as the breadth of the storyteller's craft. For tales told in Cajun and Creole French, Koasati, and Spanish, the editors have supplied both the original language and English translation.